Evaluation of the efficacy of angiotensin receptor–neprilysin inhibitor in patients with aortic stenosis undergoing transcatheter aortic valve implantation: protocol for a randomised, open-label, controlled study - Hideki Hanaoka; Yoshio Kobayashi; Hideki Kitahara; Takeshi Sugawara; Goro Matsumiya; Yosuke Inaba; Shogo Okita; Hiroaki Yaginuma; Hiroki Goto; Hiroaki Yamamoto; Tomoyoshi Kanda; Kaoru Matsuura (BMJ Open)
Introduction There are a substantial number of patients developing heart failure after transcatheter aortic valve implantation (TAVI) for severe aortic stenosis (AS), even though AS has been successfully treated. The purpose of this randomised controlled trial was to determine whether the addition of an angiotensin receptor–neprilysin inhibitor (ARNI), sacubitril/valsartan, is superior to conventional medications in lowering N-terminal pro-B-type natriuretic peptide (NT-proBNP) levels in patients undergoing TAVI for AS.Methods and analysis The study design is a prospective, single-centre, open-label, randomised, parallel-group, two-arm study, in which participants will be randomised in a 1:1 ratio to receive either conventional medications plus ARNI or conventional medications only. In the ARNI group, if a patient was on an ACE inhibitor or angiotensin II receptor blocker before TAVI, it will be switched to ARNI 100 mg/day (50 mg two times per day) on the first postoperative day. If not, candesartan 4 mg/day will be started 1–2 days before TAVI, and switched to ARNI 100 mg/day on the first postoperative day. As the patient has tolerability to ARNI, dosage will be increased stepwise to 400 mg/day 2–4 weeks apart. ARNI will be continued until at least 6-month follow-up. In the control group, the patient will receive conventional medications. The primary endpoint is the serum NT-proBNP value at 6-month follow-up after TAVI. Each group includes 42 patients (84 total patients).Ethics and dissemination Ethical approval for this study has been obtained from the Chiba University Hospital Certified Clinical Research Review Board (CRB3180015). The study is ongoing. Findings from this study will be disseminated through peer-reviewed publications and conference presentations.Trial registration number This trial has been registered on the Japan Registry of Clinical Trials: jRCT1031220344.